Instrument development: Entrepreneurial Social Support Assessment Instrument (IESSA) - Sahban, Muhammad Amsal; Kumar M., Dileep; Sri Ramalu, Subramaniam (TIJRP, 2015)
ABSTRACT There are many researchers contributed to study the role of social support systems in grooming young graduate to become entrepreneurs. However, these findings are topic specific not integrating varied models proposed by various authors in entrepreneurship.Many aspects like family, peer group, educational institutions, etc. have keen role in acting as a factor of social support system.It has been pointed out by Susanti (2012) that someone who dares to choose entrepreneurship as a career is a person who feels being trusted by people, feel comfortable, able to deal with any risks.Such behavior can grow and thrive in the person who receives social support. All these researchers have pointed out the importance of social support system in grooming students to become young entrepreneurs.However, there are less number of studies have been conducted in Indonesian scenario to identify which are the variables that are closely knit with the social support theme in its contribution toward entrepreneurship among young graduates. Hence, contemporarily a study needs to be conducted by examining various models, theories, and recent review of literature, contextualizing the topic into Indonesian business school.In this context, an instrument was developed to measure factors of social support and particularly focusing on individual factors, in the education sector. The process of instrument development was initially conducted through qualitative method and followed by quantitative method. The study adopted various techniques including content analysis, and personal interviews with the students, followed by focused group discussion and Delphi technique with expert. After identifying the variables through Delphi technique, the variables were tested to meet the validity and reliability through quantitative method. This study utilized content, construct and face validity to validate sub-factors and items generated in the instrument. It was finalized that there are 25 items under 2 sub-factors of entrepreneurial social support. Introduction Social support is a concept which is widely deliberated and discussed across the globe. However, there are less number of studies have been conducted in Indonesian scenario to identify which are the variables that are closely knit with the social support theme in its contribution toward entrepreneurship among young graduates.It is undeniable that social support system is pivotal for university students in Indonesia, this support can enhance their motivation to involve in entrepreneurship. However, most of the students seldom obtain such support in their environment. There is a thought that many parents expect their children become civil servants then their life would be better than to be entrepreneurs (Mustikawati & Bachtiar, 2008).This statement is really tragic if it is linked to Indonesian economy with a high rate of unemployment and lack of job opportunities.A good entrepreneurial environment and good social support, in fact, will be able to overcome this severe problem. However, it is not that simple to start a new business in Indonesia. Many people who are engaged in small business like street ventures, small shoppers, etc. are perceived as almost equal to unemployed and are not considered as good ventures by the Indonesian community.While these small businesses are extending better turnover and good return on investment to the business starters.Here, the small ventures are associated with social stigma that these entrepreneurial jobs are less prestigious as a government job.Whereas, it is obvious that when someone intends to pioneer new business, he desperately needs a